(untitled) (Journal of Foreign Language Studies, 2024)
Kanji, along with Hiragana, Katakana and Latin, is a type of ideogram used in the modern Japanese writing system. However, Kanji is composed of many writing strokes with different pronunciation, making it difficult for students to learn Kanji. This study presents the current teaching and learning of Kanji among first-year students at the Japanese Language Department, Hanoi University. Based on the survey findings, statistical results and data analysis, this study analyzes students’ Kanji learning and practice methods and thence proposes some solutions to teaching Kanji to help improve the effectiveness of Japanese teaching and learning.